1992
DOI: 10.1055/s-2006-961545
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntimalarial Activity and Chloroquine Potentiating Action of Two Bisbenzylisoquinoline Enantiomer Alkaloids Isolated fromStrychnopsis thouarsii and Spirospermum penduliflorum

Abstract: The bisbenzylisoquinolines 7-O-demethyltetrandrine and limacine, respectively, isolated from Strychnopsis thouarsii Baill. and Spirospermum penduliflorum Thou. were evaluated for their intrinsic antimalarial activity in vitro and chloroquine potentiating action against the chloroquine-resistant Plasmodium falciparum FCM 29 originating from Cameroon. They both showed significant antiplasmodial potency in vitro with very similar IC50 values of respectively, 740 nM and 789 nM (IC50 = 214 nM for chloroquine used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 6 publications
2
8
0
1
Order By: Relevance
“…We previously reported that the bisbenzylisoquinoline alkaloids frangchinoline and limacine isolated from plants used as adjuvants to CQ have both significant in vitro intrinsic antiplasmodial potency and CQ enhancement activity (15). In the present study, we have found that strychnobrasiline and malagashanine lack in vitro intrinsic antimalarial activity but enhance in vitro CQ effectiveness against a CQ-resistant strain of Plasmodium falciparum.…”
Section: Cyto Toxicity Testsupporting
confidence: 48%
“…We previously reported that the bisbenzylisoquinoline alkaloids frangchinoline and limacine isolated from plants used as adjuvants to CQ have both significant in vitro intrinsic antiplasmodial potency and CQ enhancement activity (15). In the present study, we have found that strychnobrasiline and malagashanine lack in vitro intrinsic antimalarial activity but enhance in vitro CQ effectiveness against a CQ-resistant strain of Plasmodium falciparum.…”
Section: Cyto Toxicity Testsupporting
confidence: 48%
“…Investigation of some such plants in Madagascar has shown that they reverse chloroquine resistance in vitro and in mouse models [70]. These include bisbenzylisoquinoline alkaloids of Strychnopsis thouarsii and Spirospermum penduliflorum [87], alkaloids of Hernandia voyronii [88], and strychnobrasiline and malagashanine from Strychnos myrtoides [89]. Three indole alkaloids, icajine, strychnobrasiline and isoreticuline from Strychnos icaja , S. myrtoides and S. variabilis , which have no intrinsic anti-malarial activity, have been shown to reverse chloroquine resistance in in vitro tests with P. falciparum [90].…”
Section: Multidrug Resistance Inhibitorsmentioning
confidence: 99%
“…Spirospermum penduliflorum was mainly studied for its antiplasmodial alkaloids content but also for its vasorelaxant activity (Raoelison et al 2013;Ratsimamanga-Urverg et al 1992). However, this plant was never studied for its antimicrobial activity.…”
Section: Spirospermum Penduliflorum Thouars (Menispermaceae)mentioning
confidence: 99%